Innovative approach and operational issues of animation services in hotels - Bortnitskaya, Miroslava; Tyshchenko (Usatiuk), Olena; Tsyrulnikova, Vita; Chagayda, Andriy (My University, 2017)
The objective of this study was to gain a better knowledge of managerial and operational issues of resorts’ animation and entertainment services. Animation programs provided by resorts are typically designed to meet the specific needs and wishes of two distinctive guest-segments – children and adults. Hotel businesses implement animation programs to increase market profile and attract repeat clientele; hence, from a business perspective. Since growing interest in active recreation and diverse entertainment is a persistent trend in the vacation industry, resort managers should, however, treat animation programs as an important service component with large potentials to enhance the overall resort experience. Досліджено управлінські та операційні питання анімаційних та розважальних послуг курортних готелів. Анімаційні програми розроблені таким чином, щоб задовольнити особливі потреби та побажання двох відмінних гість-сегментів – дітей та дорослих. Готельні підприємства впроваджують анімаційні програми, щоб розширити контингент споживачів. Оскільки, зростаючий інтерес до активного відпочинку та різноманітних розваг є стійкою тенденцією, доцільно розглядати анімаційні програми як перспективний напрямок розвитку готельних підприємств.
Keywords: animation services; activity; hotel; resort; анімаційні послуги; активність; готель; курортний готель; кафедра готельно-ресторанної справи